Economic assessment of water storage for adaptation to climate change in Sub-Saharan Africa - Xenarios, Stefanos; McCartney, Matthew P.; Polatidis, H.; Eguavoen, I. (2011)
The development of water storage schemes in Sub-Saharan Africa is considered a major aid for agricultural regions with scarce water and anticipated climate change impacts. The selection of storage options is often conducted through monetary assessment of direct costs and benefits. Such an approach, although prompt and straightforward, often leads to reductionism in the assessment process and loss of valuable information. This in turn can result in less than optimal decision-making. Against this background, this paper proposes an alternative approach based on an outranking methodology designed with thresholds and weighting values. Though based on the underlying principle of economic efficiency, the approach proposed avoids some crucial weaknesses of cost-benefit analysis and places greater emphasis on socioeconomic and environmental criteria. The method has been evaluated in six case studies conducted in Ethiopia and Ghana.